Molecular Typing of Methicillin-Resistant Staphylococcus aureus: Can PCR Replace Pulsed-Field Gel Electrophoresis? - Strandén, A. (American Society for Microbiology, 2003)
Pulsed-field gel electrophoresis (PFGE) is considered the “gold standard” for molecular typing of methicillin-resistant Staphylococcus aureus (MRSA). However, the method is time-consuming and expensive, and its discriminatory power may not be necessary in outbreak situations. We used a rapid multiplex PCR-based method with published primers and compared the results with those obtained by PFGE. A total of 75 clinical isolates were typed: 59 strains originated from our prospectively collected clinical strains and were epidemiologically unrelated; 16 strains came from an outbreak that was epidemiologically well defined in time and space. A primer mix of the spa gene, the coa gene, and the hypervariable region adjacent to mecA gene was used for multiplex PCR. Both PFGE and PCR clustered the 75 strains into 41 different genotypes. Concordance of the results was 100% for strains originating from the outbreak. Overall, both methods produced concordant results in 72% of cases. A total of 16% were clustered together by PFGE, but not by PCR and 12% were clustered together by PCR but not by PFGE, respectively. The turnaround time was only 8 h for PCR but 5 days for PFGE. This PCR-based method is excellent for rapid and inexpensive typing of MRSA in an outbreak setting, but the discriminatory power and reproducibility are still insufficient to replace PFGE in longitudinal studies in the endemic setting.